Pathet Gunem Tradition in Javanese Wedding from the Perspective of Islamic Law - Fadilah, Nur; Ismayawati, Any (Program Studi Hukum Keluarga Islam, 2024)
In Javanese society, there are several traditions that initiate the marriage process. One of them is the Pathet Gunem tradition carried out by the people of Banowan Village. This research aims to find out how the Pathet Gunem tradition proceeds, what the goals of the Pathet Gunem tradition are and how the Islamic legal perspective views the Pathet Gunem tradition. The research uses a qualitative approach, the data sources used in the research are primary data and secondary data. Primary data was obtained from interviews with various informants, while secondary data was in the form of al-qur’an, of laws and articles. The research results show that Pathet Gunem is the final result of deciding on a word, usually done a month or several months before the wedding. Pathet Gunem is a deliberation between the parents of the man and woman to discuss wedding preparations, with the aim of getting clarity on the day, date, time, place and other things related to the wedding day event. The aim and benefits for both families are to avoid misunderstandings between the two parties and for the two families to get to know each other. From an Islamic legal perspective, the Pathet Gunem tradition does not require a marriage to be valid. Pathet Gunem is a Javanese wedding tradition, not the main requirement for marriage.